2018
DOI: 10.1038/s41534-018-0115-x
|View full text |Cite
|
Sign up to set email alerts
|

Observation of non-locality sharing among three observers with one entangled pair via optimal weak measurement

Abstract: Bell nonlocality plays a fundamental role in quantum theory. Numerous tests of the Bell inequality have been reported since the ground-breaking discovery of the Bell theorem. Up to now, however, most discussions of the Bell scenario have focused on a single pair of entangled particles distributed to only two separated observers. Recently, it has been shown surprisingly that multiple observers can share the nonlocality from an entangled pair using the method of weak measurement without postselection [Phys. Rev.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 43 publications
(56 reference statements)
2
53
0
Order By: Relevance
“…This makes our results readily applicable to experimental applications. Such tests are well within the state-ofthe-art experiments [30][31][32]. Moreover, we notice that the class of quantum instruments self-tested in this work are precisely those implemented by the experimental realisations in [30][31][32][33].…”
Section: Discussionmentioning
confidence: 69%
“…This makes our results readily applicable to experimental applications. Such tests are well within the state-ofthe-art experiments [30][31][32]. Moreover, we notice that the class of quantum instruments self-tested in this work are precisely those implemented by the experimental realisations in [30][31][32][33].…”
Section: Discussionmentioning
confidence: 69%
“…Moreover, they showed that an arbitrary long sequence of Bobs can establish nonlocal correlations with Alice, given that their measurement inputs are judiciously biased. This motivated further work exploring the potential of these ideas for randomness generation [13] and their classical communication cost [14], and led to experimental demonstrations [15,16]. More recently, these ideas were extended to other types of quantum correlations [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Note added -While we were completing our work we became aware that a similar manuscript, showing the experimental violation a double Bell inequality, was recently posted on arXiv [17]. particular, for small angle θ of the thin glass plate we can omit the refraction and consider the following model for φ…”
mentioning
confidence: 99%